Vibrio parahaemolyticus has a homolog of the Vibrio cholerae toxRS operon that mediates environmentally induced regulation of the thermostable direct hemolysin gene. - Lin, Z (1993)
In an effort to identify the regulatory gene controlling the expression of the tdh gene, encoding the thermostable direct hemolysin of Vibrio parahaemolyticus, we examined total DNA of AQ3815 (a Kanagawa phenomenon-positive strain) for sequences homologous to that of the toxR gene of Vibrio cholerae. The extracted DNA gave a weak hybridization signal under reduced-stringency conditions with a toxR-specific DNA probe. Cloning and sequence analysis of the probe-positive sequence revealed an operon (Vp-toxRS) which was highly similar to the toxRS operon of V. cholerae (Vc-toxRS) (52 and 62% similarities in the two genes, respectively). The deduced amino acid sequences of the Vp-toxRS gene products (Vp-ToxRS) contained regions similar to the proposed transmembrane and activity domains of the Vc-toxRS gene products (Vc-ToxRS). All clinical and environmental strains of V. parahaemolyticus examined possessed the Vp-toxRS genes. In the presence of Vp-ToxS, Vp-ToxR promoted expression of the tdh2 gene, one of two tdh genes (tdh1 and tdh2) carried by Kanagawa phenomenon-positive strains. The DNA sequence located 144 bp upstream of the tdh2 coding region was shown to be important for the Vp-ToxR-stimulated expression of the tdh2 gene in an Escherichia coli background. Comparative analysis of AQ3815 and its isogenic Vp-toxR null mutant gave the following results: (i) Vp-ToxR promoted, in an AQ3815 background, expression of the tdh gene to different degrees in various culture media, with KP broth (2% peptone, 0.5% NaCl, 0.03 M KH2PO4, pH 6.2) being most effective (12-fold); (ii) the promotion of tdh gene expression in KP broth was at the level of transcription; and (iii) Vp-ToxR was essential for demonstration of enterotoxic activity of AQ3815 in the rabbit ileal loop, a model previously used to demonstrate thermostable direct hemolysin-mediated enterotoxic activity of AQ3815. These results demonstrate that Vp-ToxR and Vc-ToxR share a strikingly similar function, i.e., direct stimulation at the transcriptional level of the gene encoding a major virulence determinant (enterotoxin) of a Vibrio species.